Time domain simulation of soil foundation structure interaction in non-uniform soils. - Jeremić, Boris (Earthquake engineering & structural dynamics.)
Presented here is a numerical investigation of the influence of non?uniform soil conditions on a prototype concrete bridge with three bents (four span) where soil beneath bridge bents are varied between stiff sands and soft clay. A series of high-fidelity models of the soil?foundation?structure system were developed and described in some details. Development of a series of high-fidelity models was required to properly simulate seismic wave propagation (frequency up to 10Hz) through highly nonlinear, elastic plastic soil, piles and bridge structure. Eight specific cases representing combinations of different soil conditions beneath each of the bents are simulated. It is shown that variability of soil beneath bridge bents has significant influence on bridge system (soil?foundation?structure) seismic behavior. Results also indicate that free field motions differ quite a bit from what is observed (simulated) under at the base of the bridge columns indicating that use of free field motions as input for only structural models might not be appropriate. In addition to that, it is also shown that usually assumed beneficial effect of stiff soils underneath a structure (bridge) cannot be generalized and that such stiff soils do not necessarily help seismic performance of structures. Moreover, it is shown that dynamic characteristics of all three components of a triad made up of earthquake, soil and structure play crucial role in determining the seismic performance of the infrastructure (bridge) system.